Application of edible film from chitosan as biodegradable packaging. Issue 1 (February 2021) - Saputra, E; Tjahjaningsih, W; Abdillah, A A
Abstract: The application of film on the African catfish burger stored at room temperature can maintain the quality of the African catfish burger in terms of water content, protein content, fat content, ash content, water activity, and TPC (total plate count) and organoleptic values. Based on these parameters, it can be concluded that the African catfish burger wrapped in the edible film can last up to two days of storage at room temperature.